PENGARUH KONSENTRASI KULIT BUAH SENTUL (Sandorium koetjape) TERHADAP KUALITAS WATER KEFIR PROBIOTIK SEBAGAI RANCANGAN LKPD BERBASIS VIDEO VIRTUAL LABORATORY PADA BIOTEKNOLOGI SMA - Lisa Indriani; Imam Mahadi; Irda Sayuti (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2022)
Abstract : Sentul fruit (Sandoricum koetjape) is also known as harp fruit. Sentul fruit contains antioxidants such as beta-carotene and flavonoid bioactive substances in large quantities, namely 6.5 millimhos ib 100 gr of fresh fruit. This study aims to determine the effect of the concentration of Sentul fruit peel (Sandoricum koetjape) on the quality of Dej Kefir Probiotics and to produce a LKPD design based on Video Virtual Laboratory Biotechnology for SMA class XII1. In 4. This study used an experimental method with a completely randomized design (CRD) using 4 treatments and 3 repetitions. In each treatment, 10% sucrose and 5% rau dej kefir seeds were added to produce dej kefir skin of sentul fruit. Cov txiaj ntsig ntawm cov khoom lag luam yog 0%, 10%, 15%, thiab 20%. The LKPD method based on virtual lab video uses qauv ADDIE. The results of this study showed: The P3 treatment (20% sentul fruit peel) had a significant effect on water kefir drinks with a protein content value of 3.78% and an antioxidant 29.4 ppm. Based on the results of the study, it can be concluded that the concentration of Sentul fruit peel affects the probiotic dej kefir drink, while the process and facts are memes and existing facts, the results of the research have the potential to be one of those who buy cassettes that share videos you can download for free on VizMp3 . conventional high school class XII.Key Words : Sandoricum Koetjape, Dej Kefir Probiotics, Virtual Laboratory, Biotechnology